Noble gas signatures in Greenland : tracing glacial meltwater sources - Niu, Yi; Castro, M. Clara; Aciego, Sarah M.; Hall, Chris M.; Stevenson, Emily I.; Arendt, Carli A.; Das, Sarah B. (Geophysical Research Letters, 2015)
Author Posting. © American Geophysical Union, 2015. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Geophysical Research Letters 42 (2015): 9311–9318, doi:10.1002/2015GL065778. This study represents the first comprehensive noble gas study in glacial meltwater from the Greenland Ice Sheet. It shows that most samples are in disequilibrium with surface collection conditions. A preliminary Ne and Xe analysis suggests that about half of the samples equilibrated at a temperature of ~0°C and altitudes between 1000 m and 2000 m, with a few samples pointing to lower equilibration altitudes and temperatures between 2°C and 5°C. Two samples suggest an origin as melted ice and complete lack of equilibration with surface conditions. A helium component analysis suggests that this glacial meltwater was isolated from the atmosphere prior to the 1950s, with most samples yielding residence times ≤ 420 years. Most samples represent a mixture between a dominant atmospheric component originating as precipitation and basal meltwater or groundwater, which has accumulated crustal 4He over time. University of Michigan; Packard Foundation; Department of Earth and Environmental Sciences Turner fellowship 2016-05-06